Analysis Deformation Monitoring Techniques Using GNSS Survey and Terrestrial Survey ( Case Studi: Diponegoro University Dam, Semarang, Indonesia). (August 2019) - Yuwono, B D; Prasetyo, Y
Abstract: Global Navigation Satellite Systems (GNSS) are recently used in deformation monitoring aplications, e.g., estimating infrastructure and motion of crustal plate. The new improvement of GNSS instruments which allow high-precision with 24 hours availability data processing. Deformation measurement techniques were considered and mostly used by geodesy specialist will be reviewed. The need of doing the deformation measurements periodically in engineering structures will be emphasised. In this research, monitoring displacement on a dam structure were conducted using GNSS survey and terestrial survey base on Total Station and Waterpass. Analyses will be carried out with the focus of assessing the position precision that can be acquired using GNSS and terrestrial survey. This paper also emphasize the role of GNSS and terestrial application in deformation especially for dam monitoring.